Mohammad El-Shahawi Redox Impulse and Electrochemical Sensing Platform for Detection of Parathion Residues in Water using Au- Nanoparticles-Anchored Nafion Nano composites Modified Glassy Carbon Electrode - El-Shahawi, Mohammad; Alhogbi, Basma; Alwael, Hassan; Asiri, Najwa (Journal of King Abdulaziz University: Science, 2024)
Nanomaterial adapted detection systems represents a principal driver to the adoption of electrochemical sensors for pesticides residues in water. Thus, the current strategy reports a facile and highly sensitive electrochemical probe for monitoring residual parathion (ØNO2) at trace levels in environmental water samples. The established probe was based upon the use of anchored Au nano particles (Au NPs) onto Nafion as Nano composites modified glassy carbon electrode (Au NPs/Nafion/GCE). The surface topography, effective surface area and electrocatalytic performance of the Au NPs/Nafion/GCE were evaluated. Thus, a straightforward protocol based upon combination of the modified GCE and square wave- adsorptive cathodic stripping voltammetry (SW-Ads SV) at pH 7.0 was established for detection of trace levels of parathion in water. Common pesticides and inorganic ions in water did not interfere in parathion detection. Under the optimal parameters, the established method gave two linear responses of the catholic peak current (ip,c) at -0.8 V versus parathion concentrations were linear over wide concentration ranges from 1.07 × 10-6 - 1.07 × 10-5 and 1.99 × 10-9 - 9.0 × 10-7 M with the low limits of detection (LOD) and quantification (LOQ) of 6.06 × 10-10 M and 2.0 × 10-9 M, respectively. The established probe displayed excellent reproducibility, repeatability, and acceptable levels of relative standard deviation (RSD) of ±0.5 % (n=5) at 8.0 × 10-7 M of parathion. The developed probe was applied for detection of parathion residues in environmental samples, and the results were favorably validated by comparison with the standard HPLC method. The Student texp and Fexp statistically analyzed the data and the values have revealed good precision and independency of the developed probe.